Running speed in soccer - Buschmann, J.; Rehhagel, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
This lecture is concerned with the development of a test battery for the diagnosis and controlling of the soccer-specific run speed. Central questions are: How frequently, how importantly and of which kind are speed performances in soccer matches? How does a valid soccer-specific test look like? Are there correlations regarding acyclic as well as cyclic speed performances in soccer matches?